Advances and current concepts on Eph receptors and ephrins in upper digestive tract cancers - Lavareze, Luccas; Kimura, Talita de Carvalho; Scarini, João Figueira; de Lima-Souza, Reydson Alcides; Gonçalves, Moisés Willian Aparecido; Sales de Sá, Raisa; Aquino, Iara Gonçalves; Fernandes, Patricia Maria; Ribeiro, Fernanda Cristina Poscai; Altemani, Albina; Mariano, Fernanda Viviane; Fillmore, Gary Chris; et al. (Frontiers in Oncology, 2025)
Erythropoietin-producing hepatocellular (Eph) receptors comprise the largest group of surface receptors and are responsible for cellular signals. Eph/ephrin signaling has been identified to play a role in key cancer development and progression processes, especially in the upper gastrointestinal tract. The Eph/ephrin system has been described as a tumor suppressor in duodenal cancer, while in esophageal, gastric, hepatic, and pancreatic cancer, the system has been related to tumor progression. For their significant role in developing a wide range of malignancies, Eph receptors and their ligands have proven to be an important target for new anticancer therapies. In this review, we present an overview of the literature and highlight evidence supporting the role of the Eph/ephrin system in upper digestive tract cancers. In addition, we discuss molecular findings that represent promising therapeutic targets for these cancers.